Reconstructive surgery of traumatic skin wound of extremities in cats and dog - Mohamed Yusof, Loqman; Ibrahim Bajunid, Aina Fazlin; Jun, K. L.; A. H., Norazian; Ibrahim, Rashid (Universiti Putra Malaysia Press, 2004)
A few examples of traumatic skin defect at limb extremities of cats and dog are illustrated. The selected reconstructive surgery using various skin graft techniques with good clinical results are described.